MODEL KOLABORASI STAKEHOLDER DALAM PENGAMBANGAN. TECHNOPARK DI KOTA SEMARANG - Mustafa Mustafa; Suryani Alifah; Moch Taufik (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2020)
Techno Park is an area that have activities of science and technology development, business incubation, business support and production function in collaboration between Government, Education Institution and Industry/Business. Semarang Government has a plan to develop Techno Park so it is necessary to analyze collaboration model off stakeholders in developing technopark. This research is a qualitative descriptive study. Location of the study was conducted in the city of Semarang. Respondents were selected based on a purposive sampling technique, that is, a technique for selecting respondents to obtain data sources based on the person who was thought to know the best about what researchers expected. The results of this study Techno Park stakholders: Primary Stakeholders: Semarang Government, Startup Technology, and Education Institution, Key Stakeholders: Semarang Government and Technopark management because they have legal authority in decision making and secondary or supporting stakeholders, Ministry, provincial government, Technology based Community, Business Incubator in Semarang City, Media, Angel investors and venture capital. The choice of technoparks stakeholder in Semarang, focus areas consists implementation of technology and information in agriculture.